Could Polyphenols Really Be a Good Radioprotective Strategy? - Shadab Faramarzi; Simona Piccolella; Lorenzo Manti; Severina Pacifico (Molecules, 2021)
Currently, radiotherapy is one of the most effective strategies to treat cancer. However, deleterious toxicity against normal cells indicate for the need to selectively protect them. Reactive oxygen and nitrogen species reinforce ionizing radiation cytotoxicity, and compounds able to scavenge these species or enhance antioxidant enzymes (e.g., superoxide dismutase, catalase, and glutathione peroxidase) should be properly investigated. Antioxidant plant-derived compounds, such as phenols and polyphenols, could represent a valuable alternative to synthetic compounds to be used as radio-protective agents. In fact, their dose-dependent antioxidant/pro-oxidant efficacy could provide a high degree of protection to normal tissues, with little or no protection to tumor cells. The present review provides an update of the current scientific knowledge of polyphenols in pure forms or in plant extracts with good evidence concerning their possible radiomodulating action. Indeed, with few exceptions, to date, the fragmentary data available mostly derive from in vitro studies, which do not find comfort in preclinical and/or clinical studies. On the contrary, when preclinical studies are reported, especially regarding the bioactivity of a plant extract, its chemical composition is not taken into account, avoiding any standardization and compromising data reproducibility.